Formation of Diagnostic Competencies of the Future Teacher-Psychologists in the Context of Inclusive Education - Kakarova , Turshakiz (Pedagogy and Psychology, 2025)
The development of inclusive educational practice in the Republic of Kazakhstan, where over 68,000 children with special educational needs are integrated into mainstream educational institutions, necessitates a reconceptualisation of the professional preparation of educational psychologists in the formation of diagnostic competencies. Methodology and Methods. Methods of theoretical analysis of domestic and international research in the field of professional readiness of educational psychologists were employed. A structured interview study was conducted with 5 lecturers to examine current issues in the preparation of prospective educational psychologists. Results. The structure of diagnostic competencies was determined, comprising cognitive, operational, and personal elements. Distinctive features of psychodiagnostic work with various nosological groups of children were identified. Directions for modernisation of the educational process were analysed: expansion of the practical component, integration of digital technologies, and development of a supervisory support system. Scientific Novelty. Requirements for diagnostic competencies of educational psychologists within the context of inclusive educational environments were analysed. Practical Significance. The research findings may be utilised for enhancing educational programmes for the professional preparation of future educational psychologists in the development of diagnostic competencies.